Knowledge, perceptions and practices on healthcare waste management and associated occupational health hazards among healthcare professionals in the Colombo District, Sri Lanka: a cross-sectional study - Udayanga, Lahiru; Sahana, Loganatahan; Perera, Ayesha; Ranasinghe, Koshila; Ranathunge, Tharaka (Frontiers in Public Health, 2023)
Background: Proper Healthcare Waste (HW) management is directly influenced by the knowledge and attitudes of Healthcare Professionals (HCP). However, studies that characterize the knowledge and practices of HCP on HW management are limited in Sri Lanka. This study was conducted to characterize the knowledge, perceptions and practices of HCP on the management of HW and to determine the risk factors influencing HW related occupational health hazards in the Colombo District of Sri Lanka. Methods: A total of 407 HCP were recruited as the study population from selected hospitals in the Colombo District. Information on socio-demographic factors, knowledge, attitudes and practices on HW management were gathered using an interviewer-administrated questionnaire. The Binary Logistic Regression (BLR) was used to determine the socio-economic risk factors associated with the occurrence of HW related health issues among the respondents. Results: The majority of respondents were characterized with a high knowledge level (76.9%) and positive attitudes (53.8%) on HW management. Incineration (82.6%) was recognized as the most widely used HW treatment method. Personal Protective Equipment (PPE) was used at a satisfactory level (85.5%), while liquid waste treatment was limited (57.5%). The occupational designation, level of training received in HW management, professional experience, vaccination status for tetanus, degree of knowledge and attitudes on HW management were recognized as significant risk factors (P<0.05) associated with the occurrence of HW related occupational hazards. Conclusions: Even though, the treatment of HW was satisfactory, strengthening the existing mechanisms for monitoring of HW management, provisioning more resources and organizing training and awareness programmes on HW management for HCP are recommended.